STUDI KARAKTERISTIK DAERAH ALIRAN SUNGAI (DAS) SENAKIN KECAMATAN SENGAH TEMILA - Asdiwar, Flapianus; Haji, Ir. H. Riduansyah, MP.; Junaedi, Ir. Junaidi, MP. (Jurnal Sains Pertanian Equator, 2013)
A STUDY OF WATERSHED CHARACTERISTICS IN SENAKIN SENGAH TEMILA DISTRICT Flapianus Asdiwar (1), Ir. H. Riduansyah, MP (2) and Ir. Junaidi, MP (2) (1) a student of agriculture faculty and (2) staff of lecturers at agriculture faculty of Tanjungpura University, Jl. A. Yani Pontianak 78124 ABSTRAK The purpose of this research was to figure out the watershed characteristics in Senakin which possessed the widespan of 16.192,98 ha and it was one of the watersheds which was located in Sengah Temila District, Landak Regency, Kalimantan Barat. This research consist of two stages. The first which was conducted on the field to observe and to take a bottle of water as sample a day in 5 days period. Then it was continued to the next stage which was conducted in the Soil, Water, And Environment Analysis Laboratory to analyze the sample. The result of this research showed that the drainage pattern and the watershed shapes took dendritics pattern and elongated, whereas the river transverse profile took triangular form. The river’s orde consists of three orders with drainage density index as mush 2,20 which included into medium category, the water quality in watershed Senakin possed average pH as much 5,67 which classified as good, and the average temperature as much 280 C which was considered as normal. While the wataer brightness in Senakin watershed as much 30,6 cm. After lab analysis was obtained by comparing the average TSS in the outlet with standard TSS for agriculture, then the value of average TSS in Senakin watershed was 9,40 which categorized as good. Keywords: Characteristics, Watershed, Senakin.